Pengaruh Polimer dan Peningkat Penetrasi Terhadap Karakter Penetrasi Matriks Sediaan Patch Transdermal Karvedilol - Untia Kartika Sari Ramadhani; Joshita Djajadisastra; Iskandarsyah Iskandarsyah (Fakultas Farmasi Universitas Pancasila, 2017)
Carvedilol is β-blocker antihypertensive drug with low oral bioavaibility and short half time which causes the frequency of oral drug used more often or the oral dose might be increased. Transdermal patch with the matrix system can deliver drug through skin in controlled within specifi c time period and hopefully it can improve carvedilol bioavaibility and convenience for patients.The aim of research was to fi nd out the effect of polymer and penetration enhancer toward penetration characteristic of carvedilol transdermal patch matrix seen from kinetics release data and penetration data of carvedilol. The polymer ratio of Polyvinyl Alcohol (PVA) : Ethyl cellulose (ES) polymers and Sorbitan Monolaurate (SM) as penetration enhancer concentrations used were F1 (1:1) / 8%, F2 (1: 1) /10%, F3 (2:1) /8%, F4 (2:1)/10%. Formula F1 did not pass in the organoleptictes so next test only carried out for formula F2, F3 and F4. The in vitro release of carvedilol showed formula F2, F3 and F4 lasted for 24 hours and the released kinetics of carvedilol followed the order of 0 and Higuchi. Carvedilol % cumulative from penetration test in vitro showed for F2, F3 and F4 formulas respectively were 15,384%, 16,495% and 18,287%.